Potential of Septoria araujiae (Capnodiales: Mycosphaerellaceae) as a classical biocontrol agent for moth plant, Araujia horto - Ramirez, Gustavo Hernán (2023)
Araujia hortorum (Apocynaceae) is native to Argentina where it is appreciated for its medicinal, nutritional, and ornamental value. In several countries where it has been introduced for the latter, it has become an invasive weed, and in the case of New Zealand it has been declared a target for classical biological control. The rust fungus Puccinia araujiae is, to date, the most studied of its fungal pathogens and shows very good prospects as a biocontrol agent. Nevertheless, little is known about the other pathogens that affect this plant in its native range. Studies are being conducted to build a body of knowledge on the fungal diseases affecting A. hortorum in Argentina. Surveys were carried out in the province of Buenos Aires in search of plants with symptoms of disease. In several populations across the province, plants were observed to be severely damaged by a foliar disease which was found to be associated to Septoria araujiae (Fungi, Ascomycota). Diseased plants exhibited extensive angular necrotic leaf spots, and in some cases, extensive necrotic areas on fruit surfaces. A detailed morphological description of the fungus was made, and its pathogenicity and specificity investigated, together with its penetration mode and the optimum incubation conditions for infection and disease to occur. To this end, artificial inoculations were performed on healthy plants of A. hortorum and nine other species within the Apocynaceae under controlled environmental conditions. All inoculated A. hortorum plants developed symptoms 14 days after inoculation at 20ºC. The fungus was re-isolated from affected leaves, thus fulfilling Koch´s postulates. Infection was shown to occur directly through the epidermis. Four other species belonging to the genera Araujia and Oxypetalum were found to be susceptible to the disease, indicating the fundamental host range of the pathogen is circumscribed to the subtribe Oxypetalinae. Septoria araujiae may be considered as a prospective biological control agent for A. hortorum due to its high virulence and its narrow host range. Furthermore, it was found to have quite a wider geographical distribution than P. araujiae in the province of Buenos Aires, indicating its ability to infect the host under a wider range of environmental conditions, and thus to impose a negative pressure on the host at locations where the rust may not. It is therefore suggested as an interesting potential complementary biocontrol agent.